Review on Intrusion Detection System Based on The Goal of The Detection System - Khaleel, Mohammad Khamees; Ismail, Mohd Arfian; Yunan, Umar; Kasim, Shahreen (International Journal of Integrated Engineering, 2018)
An extensive review of the intrusion detection system (IDS) is presented in this paper. Previous studies review the IDS based on the approaches (algorithms) used or based on the types of the intrusion itself. The presented paper reviews the IDS based on the goal of the IDS (accuracy and time), which become the main objective of this paper. Firstly, the IDS were classified into two types based on the goal they intend to achieve. These two types of IDS were later reviewed in detail, followed by a comparison of some of the studies that have earlier been carried out on IDS. The comparison is done based on the results shown in the studies compared. The comparison shows that the studies focusing on the detection time reduce the accuracy of the detection compared to other studies.